Informed consent for voluntary counselling and testing for HIV infection in South African mothers and children: An assessment of burdens and consequences and an argument for a modification in the process of informed consent - Roux, Paul (Centre for Bioethics, 2016)
The HIV / AIDS epidemic is devastating Africa. The continent lacks the material resources to treat infected persons or to support those affected by the epidemic. One great resource in Africa is the cohesive strength of families. Because of a fear of stigma, HIV infected persons tend not to disclose their diagnosis to their families. This non-disclosure perpetuates stigma, because ordinary people do not discover that their own family may be affected by the epidemic. Non-disclosure also results in the loss of specific family support to infected individuals and the loss of general family support as a national resource. The standard method of taking informed consent prior to HIV testing of pregnant mothers has the effect of enhancing non-disclosure, because of its inherent focus on the patient as an isolated, autonomous decision maker. This dissertation advances the thesis that an alteration in the process of informed consent, to involve the family in deliberation prior to consent, will facilitate disclosure of an HIV-positive diagnosis to the family. Disclosure will have the positive effects firstly of giving the mother access to the emotional support of her family and secondly of serving to educate the family, and through the family society as a whole, that ordinary, virtuous women can be infected with HIV.